Powertoon clues / Hanis Kamarudin ... [et al.] - Kamarudin, Hanis; Abdul Malek, Nur Ain; Ayub, Siti Ainul Ayzan; Mohamad Ghazali, Izlin; Wan Mohamed, Wan Nazihah (Universiti Teknologi MARA Shah Alam, 2018)
Reading is an important learning area which ESL learners should master for interaction and academic purposes. However, ESL students are facing many difficulties in English reading skills particularly contextual clues. Hence, this product aims to ease the teaching and learning of inferring word meaning - contextual clues, to enrich the students' vocabulary bank and to motivate the students to engage in reading. The challenge in teaching contextual clues is that the current technology-integrated teaching method has lost its way to cater students' interest in reading. This product is believed to allow the students to enjoy meaningful language classes. The emergence and usage of PowToon in today's classroom has helped to ease the process of teaching reading skills to the students. The features of this product include captivating graphics, lively animation, concise content and attractive background music. This product is user friendly as it is accessible to everyone; online and offline. İn addition, it is suitable to be used in language classes with limited technology support. Thus, this evolution in teaching pedagogy will encourage paperless teaching aids in language classrooms.